Nano-Silica-Modified Concrete: Analysis and Comprehensive Review of Material Properties and Its Use in Civil Engineering Industries (London Journal of Engineering Research, 2026)
Among the most widely used additive cementitious materials (SCMs) applied in modern concrete production, nano-silica (NS) or silicon oxide nanoparticles ($mathrmSiO_{2}$). In this article, we will analyze all aspects related to the physical/chemical characteristics of nano-silica, the interactions within the concrete structure, and their many uses in construction engineering. We have synthesized over 25 peer-reviewed articles and analyzed the impact of the addition of NS from 1% to 6 % wt. on mechanical properties; compressive strength, flexural strength and tensile splitting strength of M40 concretes compared via a control sample free of additives being added. Additionally, we have studied the durability of M40 concretes modified with NS in terms of their chloride permeability, resistance to sulphate assault and absorption in water. Finally, we analyzed the pozzolanic effect, filler effect, hydration kinetics and refining of the interfacial transition zone. As a result of our analysis, we concluded that optimal doses of 2–4% by wt. of cement are those which maximise the improvements in both strength and durability without impacting workability.
Keywords: civil engineering.; durability; high-performance concrete; interfacial transition zone; M40 concrete; nano-silica; pozzolanic reaction; supplementary cementitious material